Atuação dos conselhos escolares na rede municipal de ensino de Santa Maria – RS: em pauta o fortalecimento da gestão democrática - Machado, Cristina Magalhães Foletto (2018)
This study deals with the principles of democratic management based on the performance of the School Councils in the schools of the Santa Maria / RS Teaching Network, considering that the concept of educational management results from the understanding of the management of the destinations of the organizations, in consideration of the whole in relation to its parts and among them and also that the Municipal Teaching Network of Santa Maria had, in December 2003, approved the Law of Democratic Management No. 4,740, modified by Decree No. 09 of 23 of January of 2009, which instituted the autonomy of the management in the municipal schools in its financial, pedagogical and administrative aspects, establishing in this perspective the School Council as the maximum decision body in these educational units. In order to do so, the general objective prioritizes understanding how the work of school councils in the Municipal Teaching Network of Santa Maria / RS is configured, in the perspective of democratic management, in order to contribute with guidelines for the strengthening of this collegiate body. The research methodology was anchored in the qualitative approach, based on collaborative research. The bibliographical and documental researches corroborated to a greater understanding of the theoretical and legal references necessary to understand the problem extracted from the daily school life as well as to interlace with the facts observed and the data constructed through the semi-structured interviews with school counselors of four schools of the Municipal Network of Santa Maria / RS, using content analysis in the data crossing. The authors who based these methodological procedures are Ibiapina (2008), Flick (2009), Yin (2001; 2005), Lakatos & Marconi (2003), Neto (1994), Triviños (2015) and Bardin Biklen (1994). It is also found in the theoretical and legal elements thought and organized to identify the main concepts and knowledge needed to answer the research question: Bordignon (2009), Cury (2005; 2007), Dourado (2009), Freire (1997), Gadotti (2004), Libano (2011), Lück (2013a; 2013b; 2015), Paro (2001). The product of this study, therefore, culminated in guidelines for training for school counselors of the municipal schools of Santa Maria / RS. Specifically, guidelines for the continuing education of school counselors, which are subsidized by LDBEN nº 9,394 / 96 and Municipal Law No. 4,740 / 2003, consider the demands and specificities of the school contexts of this municipality, as well as potentiate the formation of the members of these collegiate bodies, since it is not enough to compose a school council and to be willing to work in a shared way, it is also necessary to have knowledge and guidance in participatory work. It was concluded that, with the formation of the members of the school councils, it becomes possible to build and consolidate the identity of the school, to generate a functionality as a social institution that meets the expectations of its public and the community of which it is a part and, as an institution of a truly democratic and participatory nature.